Hormonal contraception, sexual behaviour and HIV prevalence among women in Cameroon - Soskolne Varda (BMC Women's Health, 2008)
Abstract Background Data on the effect of contraceptive methods, other than the condom, on HIV acquisition is not clear. The aim of this study was to describe hormonal contraceptive use, sexual behaviour and HIV prevalence among women in Cameroon in order to provide baseline information for future analytical studies. Methods This is a cross-sectional descriptive study based a nationally representative sample of 4486 sexually active women aged 15–49 years who participated in the 2004 Cameroon Demographic and Health Survey. Results The overall HIV prevalence was 7.4% (332/4486). The HIV prevalence was higher in the 25–35 year age group (10.03%), urban residents (9.39%), and formerly married (18.48%), compared to their compatriots. The prevalence was lower in women with five or more living child (3.67%), women in the low wealth index category (3.79%) and women who had no formal education (3.37%). The HIV prevalence was higher among women who had two or more partners in the last 12 months (10.26%) and women who reported to have had four or more partners in their lifetime (12.40%). The prevalence of HIV was higher among current hormonal contraceptive users (6.63%) compared to the current non-users (3.06%), among ever users of hormonal contraception (13.27%) compared to the never users (7.11%). Conclusion We conclude that the prevalence of HIV among sexually active women in Cameroon varies according to sociodemographic characteristics, sexual behaviour and hormonal contraceptive use. Our findings underscore the need to counsel women using hormonal contraception to be aware that hormonal methods do not protect against HIV infection. Given the biologic plausibility of the link between hormonal contraception and HIV infection, future research should focus on carefully designed prospective studies to establish the temporal relationship and estimate the incidence of HIV infection among women using and not using hormonal contraceptive methods.